2013
DOI: 10.7327/cerei.2013.09.07
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the J-curve effect in the bilateral trade of Hungary

Abstract: Resulting in a J-curve pattern, the devaluation or depreciation of a currency worsens the trade balance before improving it. The aim of the paper is to investigate the J-curve effect in bilateral trade flows between Hungary and its major trading partners: Germany, Austria, Italy, France, the Netherlands, the United Kingdom, Poland and the Czech Republic. This paper explores the J-curve effect using quarterly data over the period 1997-2012. We include bilateral export and import flows, GDP and nominal bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The J-curve effect in bilateral trade between Czechia and Germany was also empirically confi rmed by Šimáková [23], who applied a traditional methodology comprised of Johansen's cointegration and error correction model. Moreover, Šimáková [36] also found the J-curve in Czechia's trade with Poland.…”
Section: Financementioning
confidence: 87%
“…The J-curve effect in bilateral trade between Czechia and Germany was also empirically confi rmed by Šimáková [23], who applied a traditional methodology comprised of Johansen's cointegration and error correction model. Moreover, Šimáková [36] also found the J-curve in Czechia's trade with Poland.…”
Section: Financementioning
confidence: 87%
“…While the existing literature about J-curve effect in the trade between European Union (EU) countries and their partners is plentiful (e.g., Hacker and Hatemi-J, 2003 ; 2004 ; Bahmani-Oskooee et al., 2006 ; Hsing, 2009 ; Hsing and Sergi, 2009 ; Šimáková and Stavárek, 2013 ; 2014 ; Nusair, 2017 ; Michail, 2018 ; Gürtler, 2018 ; Lucarelli et al., 2018 ), few studies are dedicated for Vietnam. Phan and Jeong (2015) analyzed Vietnam's trade balance with 16 partners by using Fully Modified OLS and Dynamic OLS estimators for the panel data ranging from 1999Q1 to 2012Q4 and reported that exchange rate negatively influenced trade balance and thus no J-curve effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So as to investigate the role of USD as a vehicle currency, we use the model employed by Šimáková (2013) as well as Bao and Le (2021b):…”
Section: Methodsmentioning
confidence: 99%